MONETARY POLICY, FINANCIAL SECTOR DEVELOPMENT AND POVERTY REDUCTION IN INDONESIA - Didi Nuryadin (Universitas Muhammadiyah Yogyakarta, 2006)
This paper aims to analyze the relationship between the role of monetary policy financial sector development and poverty reduction in Indonesia. Specifically, the purpose of this study investigates how the interrelationship of financial sector development and poverty reduction. This aims related with implementation of monetary policy to show further how the response of monetary policy through interest rate instrument to achieve stability of macroeconomic that Is inflation, growth and poverty reduction. The financial sector is primary conduit through which monetary policy affects real economy sector and monetary policy determines the resources available lo financial institution. Therefore, there is coordination between financial sector development and monetary policy in order to achieve final goal that is inflation, in turn, it has implication on growth and poverty reduction. The data was used in this study using time series annual data from 1970 - 2005. The source of data was taken from International Financial Statistic and Central Bank of Indonesia, The data which identified contain 3-months deposit interest rate, consumer price index, gross domestic product, domestic credit as percentage of GDP and consumption per capita as household indicator (measure of poverty). The method of analysis is vector error correction model. Impulse response and variance decomposition analysis was used to show the dynamic effect relationship within variables. The result of this study shows that domestic credit affects the poverty reduction statistically significant and positively in the long run. But in the short run, the effect of domestic credit negatively and the response of domestic credit to interest rate is positively. It is because, there is high spread interest rate margin between borrowed and lending rate, in the other side, it were caused financial intermediaries having not expand credit to ¡he pm-poor sectors of economy thus, it will influence poverty rate. The interest rate as instrument of monetary policy responds inflation significantly and it giving sign to the domestic credit. Therefore, interest rate policy must be done carefully and it needs synergy with other macroeconomics policy.